Effect of international trade on wage inequality with endogenous technology choice - Tran Lam Anh Duong (FIW - Research Centre International Economics, 2018)
This paper investigates how trade openness affects wage inequality of trading countries, both within and between them. Specifically, based on the theoretical literature on monopolistic competition between two asymmetric countries, we derive a new framework under the assumption of endogenous technology choice. This assumption implies that firms simultaneously choose to adopt different technology compositions which are appropriate for its labor composition. In other words, instead of utilizing standard constant technology as in most of other research, firms in this model are allowed to choose the technology system that maximizes their profits. With this framework, we find that firms in countries which are skilled-labor-abundant choose technologies that are appropriate for skilled labor, and vice versa for firms in unskilled-labor-abundant countries. The wage gap between different types of labor depends on the comparative level of technological capability, the skill composition in the two countries, and the skill bias. During the transition from autarky to free trade, if the size of the labor force and its composition in both countries satisfy a particular condition, we find that the decline in transport cost will increase the relative wage between one country and the other in both types of labor. Moreover, these effects on wage inequality in all phases, i.e., autarky, free trade, and the transition from autarky to free trade, are partially absorbed by the endogeneity in technology choice. In other words, if a firm utilizes a standard constant technology only, the effect on wage inequality is amplified. Based on calibration results utilizing data from 52 countries, we find that in some plausible scenarios, this amplification may generate different understandings of the role of trade openness on wage inequality.
Keywords: F16; F11; 330; international trade; endogenous technology choice; transport cost; wage inequality